The effect of Rosmarinus herbal tea on occupational burnout in Iran Chemical Industry Investment company employees - Mehrabi, Tayebe (Iran J Nurs Midwifery Res, 2015)
BACKGROUND: Burnout is one of the most important problems that the employees encounter. Many health problems arise due to burnout which is to be dealt with by the employees and the owners in the industry. Among many different ways of dealing with this problem, herbal therapy seems to be a promising solution. The present study intended to investigate the effect of Rosmarinus officinalis (RO) on burnout in employees who work in industrial environments. MATERIALS AND METHODS: An experimental study was performed to see whether RO has an effect on burnout or not. A total of 66 employees, aged between 20 and 60 years, who had worked for at least 1 year in the technical wards of Iran Chemical Industry Investment Company took part in the study. The participants were randomly assigned to two groups of control (n = 33) and RO (n = 33). The RO group received 4 g of Rosemary in 150 cc water per day for 2 months. The control group, on the other hand, did not receive anything. The data were collected via Geldard (1989) Burnout Inventory before and after the treatment. A t-test was performed to analyze the collected data. RESULTS: The results of statistical tests showed that after intervention, the score of occupational burnout in RO group was better, and a significant difference was found between the control and experimental groups (P = 0.03), in favor of the experimental group. CONCLUSIONS: The results of the study revealed that Rosmarinus had a positive effect on burnout in employees in this study. Further studies in this field are suggested.